Recruiting and retaining diverse faculty and students: Strategies for success - Majeda M. El-Banna (21480251) (2025)
Background In 2040, the United States is expected to experience a major turning point, where the proportion of people who belong to racial and ethnic minorities will expand considerably. As this demographic shift unfolds, it becomes imperative that nursing educators, students, and the nursing workforce mirror the evolving diversity of the patient population. Achieving this alignment requires a multifaceted approach. Innovation Innovative strategies are presented to effectively and intentionally recruit and retain diverse faculty and students. Implications The implications of these strategies are enormous. For faculty, the journey begins with the job description, extends through the interview process, embraces intentional recruitment practices, ensures equitable compensation, and cultivates a supportive work environment. For students, the focus involves mentorship, the creation of safe spaces, provision of support services, and comprehensive faculty training. Conclusions Employing a variety of strategies to support diverse faculty and students is instrumental in creating a more inclusive institution. Other Information Published in: Teaching and Learning in Nursing License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.teln.2025.02.034